2011
DOI: 10.1021/jf104219t
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Search Focused on Furans, Lactones, Volatile Phenols, and Acetals As Potential Age Markers of Madeira Wines by Comprehensive Two-Dimensional Gas Chromatography with Time-of-Flight Mass Spectrometry Combined with Solid Phase Microextraction

Abstract: The establishment of potential age markers of Madeira wine is of paramount significance as it may contribute to detect frauds and to ensure the authenticity of wine. Considering the chemical groups of furans, lactones, volatile phenols, and acetals, 103 volatile compounds were tentatively identified; among these, 71 have been reported for the first time in Madeira wines. The chemical groups that could be used as potential age markers were predominantly acetals, namely, diethoxymethane, 1,1-diethoxyethane, 1,1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 58 publications
4
52
0
1
Order By: Relevance
“…Significantly higher concentration of furans in these wines (Table 4) is in agreement with previous fi ndings, where furans were found to increase during maturation (35), which is favoured by the presence of lees and oxygen (6). The exclusive occurrence of the so-called oak lactones, together with the increased amounts of other identifi ed lactones in the wines produced by prolonged maceration and maturation (Table 4), most probably originated from wood, as reported previously (42). Acetals are formed during fermentation, but their content increases most signi fi cantly during oxidative conditions of maturation (35,42).…”
Section: Volatile Esterssupporting
confidence: 91%
See 2 more Smart Citations
“…Significantly higher concentration of furans in these wines (Table 4) is in agreement with previous fi ndings, where furans were found to increase during maturation (35), which is favoured by the presence of lees and oxygen (6). The exclusive occurrence of the so-called oak lactones, together with the increased amounts of other identifi ed lactones in the wines produced by prolonged maceration and maturation (Table 4), most probably originated from wood, as reported previously (42). Acetals are formed during fermentation, but their content increases most signi fi cantly during oxidative conditions of maturation (35,42).…”
Section: Volatile Esterssupporting
confidence: 91%
“…Besides that, it was previously found that the formation of ethylphenols positively correlates with maceration duration and temperature (41,42). Among benzenoids, 2-ethoxybenzyl alcohol was found only in the wines produced by prolonged maceration and maturation (Table 4).…”
Section: Volatile Estersmentioning
confidence: 79%
See 1 more Smart Citation
“…GC × GC has proven to be a powerful technique in the analysis of complex samples and to detect trace components [55,56]. Automated processing of HS-SPME/GC × GC-ToFMS data was used to tentatively identify all peaks in the GC × GC chromatogram contour plots with signal-to-noise threshold > 80.…”
Section: Structured Chromatogram and Sensitivitymentioning
confidence: 99%
“…Since its development, this technique has become very popular and gained growing acceptance and increasing use in routine laboratories applications mainly to the sampling and analysis of environmental [33], food [34][35][36], forensic [37] and pharmaceutical samples [38,39]. Typically followed by GC in combination with mass spectrometric detection (MS) [40][41][42] or its multidimensional alternative, comprehensive two-dimensional GC (GC × GC-ToFMS) [43][44][45], SPME technique has been successfully used for wine samples.…”
Section: Introductionmentioning
confidence: 99%